The impact of cooperative, group, and individual ranching systems on resource productivity in South-Central Kenya. - Onchoke, S.N. (Texas A&M University, 1986)
Government introduced livestock production systems (commercial, company, cooperative, individual, group, and grazing blocks) in Kenya's rangelands began about 15 years ago. This studyanalyizes the impact of group cooperative and individual ranching systems on resource productivity in South-Central Kenya. The issue of land subdivision of the group and cooperative ranching systems was also investigated. This was done by dividing the individual ranches into 4 strata (land area groups). The average land areas were 110, 240, 500, and 800 ha for strata 1-4 respectively. Survey results were summarized for each of the three ranching systems and the four individual ranch strata. Summary results included human and livestock populations, livestock breed composition, livestock off takes, and loaned and off-ranch grazing, annual ranch incomes and expenditures, and ranch assets. To measure livestock productivity, net returns per unit of some specified resources (people, land, and livestock) were used; hence budget analysis was adopted as the primary analytical tool for this study. Results from livestock and livestock products indi- iv cated that group ranches had positive net returns, and cooperative and individual ranches had neqative net returns. Extremely high livestock operating expenditures, particularly costs for maintenance and repairs, and high noncommercial offtake rates (largely due to high livestock mortality and slaughter for home consumption) greatly influenced the neqative net returns. The individual ranches had the lowest economic efficiency and highest physical efficiency, whereas group ranches had the reverse results. Hence, accelerated rangeland degradation would likely impact the individual ranches most because of their high livestock and human stocking rates. Individual ranches also had higher welfare status because they were found to spend more per person for home consumption, their proportion of total income spent for consumption was lower, and they had higher mean years of formal education than the group ranches. To address the cooperative and group ranch land subdivision issue, similar budget analyses were performed for the four individual ranch strata. Results revealed that stratum 4 had all positive net returns while the other three strata had negative net returns. While stratum 4 had the highest economic efficiency and lowest phYSical efficiency, stratum 1 had opposite results. Similarly, stratum 4 had the highest social welfare status and stratum 1 the lowest. Thus, group and cooperative ranch subdivision into smaller individual ranches like those in strata 1 and 2 would be both uneconomical and retrogressive to the rangeland resouces.